CL-NOTEARS: Continuous Optimization Algorithm Based on Curriculum Learning Framework - Liu, Kaiyue; Liu, Lihua; Xiao, Kaiming; Li, Xuan; Zhang, Hang; Zhou, Yun; Huang, Hongbin (Mathematics (Basel), 2024)
Causal structure learning plays a crucial role in the current field of artificial intelligence, yet existing causal structure learning methods are susceptible to interference from data sample noise and often become trapped in local optima. To address these challenges, this paper introduces a continuous optimization algorithm based on the curriculum learning framework: CL-NOTEARS. The model utilizes the curriculum loss function during training as a priority evaluation metric for curriculum selection and formulates the sample learning sequence of the model through task-level curricula, thereby enhancing the model’s learning performance. A curriculum-based sample prioritization strategy is employed that dynamically adjusts the training sequence based on variations in loss function values across different samples throughout the training process. The results demonstrate a significant reduction in the impact of sample noise in the data, leading to improved model training performance.